Structural Models of TTF and TCNQ Based on Electronic Components Linked by Plastic Tubes - Horikoshi, Ryo; Shirotani, Dai; Nakanishi-Masuno, Tsugumi; Shioyama, Hiroshi (Journal of Chemical Education, 2023)
A representative example of an organic conductor is the charge-transfer salt tetrathiafulvalene-tetracyanoquinodimethane (TTF-TCNQ). This conductor can be formed by combining TTF with TCNQ, which are both highly symmetric planar molecules that do not conduct electricity independently. In this Letter, we describe a hands-on activity on the basic chemistry of TTF-TCNQ for first-year students majoring in subjects other than chemistry. This activity introduces students to the rational design and properties of TTF-TCNQ using handmade structural models based on electronic components linked by plastic tubes. The electronic components include transistors, white LEDs, blue LEDs, and yellow LEDs, which represent sp2 carbon, hydrogen, nitrogen, and sulfur atoms, respectively. They are readily available in large quantities, which means that every student in a class can participate in the activity. The activity was tested on the participants, and quizzes were given to the participants to estimate the effectiveness of the activity. This activity helped the students understand the rational design of TTF-TCNQ.